Labour Market Institutions, Product Market Regulation, and Innovation Cross-Country Evidence - Bassanini, Andrea (OECD Economics Department Working Papers, 2002)
In this paper we present comparative evidence from OECD countries concerning the impact of product and labour market regulations on innovation. While product and labour market policies usually aim at objectives other than innovation, they may have important consequences for the profitability of firms' innovative strategies. Our regression analysis provides some cross-country evidence that enhancing competition in the product market -- while guaranteeing intellectual property rights -- seems to have a positive impact on the innovation performance of a country. Conversely, the relationship between innovation and job protection does not seem to be univocal. The sign and magnitude of the effect of the latter crucially depends on the systems of industrial relations and the specific characteristics of each industry. Indeed, the larger the scope for resorting to internal labour markets, the lower the adjustment costs imposed by labour market regulation. Moreover, in industries with a ...